2016
DOI: 10.1002/jmv.24737
|View full text |Cite
|
Sign up to set email alerts
|

EBV infection is prevalent in the adenoid and palatine tonsils in adults

Abstract: Epstein-Barr virus (EBV) is associated with the pathogenesis of several diseases in both adults and children. However, there have been no reports on the prevalence and amount of EBV in the adenoids of adults; thus, it is important to investigate these in the adenoids and tonsils of adults and children. In this study, 67 patients who underwent tonsillectomy or adenotonsillectomy were included and divided into two groups: adults aged ≥ 16 years (n = 35) and children aged <16 years (n = 32). Patients' adenoid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
7
12
0
Order By: Relevance
“…EBV prevalence among children in this study (40.6%) is in line with a reported prevalence of 43% to 50% in children in some, but not all other studies (29%‐80%; see Table ). The higher prevalence in tonsils of adults compared with children agreed with other studies evaluating tonsillar specimens . Seroepidemiologic studies are also compatible with the findings in the present study, with reported high seroprevalence (80%‐90%) in immunocompetent adults, and lower seroprevalence in children .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…EBV prevalence among children in this study (40.6%) is in line with a reported prevalence of 43% to 50% in children in some, but not all other studies (29%‐80%; see Table ). The higher prevalence in tonsils of adults compared with children agreed with other studies evaluating tonsillar specimens . Seroepidemiologic studies are also compatible with the findings in the present study, with reported high seroprevalence (80%‐90%) in immunocompetent adults, and lower seroprevalence in children .…”
Section: Discussionsupporting
confidence: 93%
“…The higher prevalence in tonsils of adults compared with children agreed with other studies evaluating tonsillar specimens. 39,40 Seroepidemiologic studies are also compatible with the findings in the present study, with reported high seroprevalence (80%-90%) in immunocompetent adults, 14,43,44 and lower seroprevalence in children. 14,45 It has, however, to be noted that data on EBV prevalence in the general population are relatively rare, and a change in EBV epidemiology has been reported over the last decades in high-income countries with decreasing overall EBV prevalence and increasing age of primary infection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In previous studies EBV DNA was found in pediatric tonsils in 43–80% of cases and in adult tonsillar tissue in 71% of cases . All these studies used PCR to detect EBV DNA copies.…”
Section: Discussionmentioning
confidence: 91%